Anesthesia in Treacher Collins Syndrome for bone anchored hearing aid (BAHA) surgery. - S. Sorrenti; E. Pisello; M. Ciuffreda; L. Brugiaferri; J. Silvestri; F. Lacchè; G. Castellana; A. Buonamico; A. Pennacchi; C. Piangatelli; D. Galante (Pediatric Anesthesia and Critical Care Journal, 2023)
Treacher Collins syndrome (TCS) is a rare genetic disor- der characterized by distinctive abnormalities of the head and face, affecting about one child in every 50000. Ab- normalities such micrognathia, cleft palate and cervical spine alterations are common and may represent an addi- tional risk in airway management for general anesthesia. As a matter of fact, difficult OTI prevalence in paediatric surgery rises from 1-2% to 50% when considering the subpopulation of paediatric patients with cervical spine diseases, as TCS ones. This article describes a case report of our anesthesiological management in bone-anchored hearing aid (BAHA) implant surgery in a 7-year-old fe- male Treacher Collins Syndrome patient born without the long process of the incus, the stapes and with hypoplasia of the oval window bilaterally. A careful preoperative evaluation and anesthesiological plan based on the use of videolaryngoscopy, routine practice in our centre, granted a successful outcome and no complications.